Hitting the Ground Running - Andrea M. Newberry-Koroluk (Critical Social Work, 2019)
This paper explores how the popular use of the expression “hitting the ground running” in reference to beginning social work practice draws upon military imagery and reflects neo-conservative expectations of first-year social workers.  Discussion of the international and Canadian definitions of social work, key social work values, the neo-conservative paradigm, and the role of language in understanding human experiences provides context to this analysis.  Ultimately, it is argued that it is in the best interests of the social work profession for the phrase hitting the ground running to be abandoned (or used critically) when making reference to first-year social workers, and a new metaphor is suggested that could take its place in the social work lexicon.